RASAL3 predicts overall survival and CD8+ T lymphocyte infiltration in lung adenocarcinoma. Issue 24 (24th November 2022) - Liang, Mei; Meng, Xiangzhi; Zhou, Boxuan; Gao, Yushun
Abstract: RAS‐activating protein‐like 3 (RASAL3) is a synaptic Ras GTPase‐activating protein (SynGAP) and a potential novel biomarker of CD8+ T cell infiltration in lung adenocarcinoma (LUAD). This study explored RASAL3 expression in LUAD, the prognostic impact of RASAL3 and the relationship with immune cell infiltration. RASAL3 expression in LUAD tissues was considerably low, with high RASAL3 expression associated with better overall survival, whereas the low expression was linked to advanced T, N, M classifications, TNM stage and lower grade. Furthermore, RASAL3 expression positively correlated with CD8+ T lymphocyte infiltration. In conclusion, RASAL3 expression is a potential prognostic and immunological biomarker of LUAD.